The Investment Interest as A Mediator Variables Towards Investment Decisions - Machella Shevany Yutama; Rahma Ulfa Maghfiroh; Agung Suryo Prakoso (Asosiasi Peneliti Manajemen Adat Indonesia, 2022)
The purpose of this study is to test Financial Attitude and Financial Literacy towards Investment Interests and Investment Decisions and to test the role of Investment Interest mediation in improving Investment Decisions. This study uses perception and causality for students. This research is a quantitative study with a survey method of positive paradigm approach. In addition, structural equation modelling is used to conduct research testing. The population of this study is students of state universities in Malang, Indonesia. This study used a Likert scale questionnaire that was distributed to 160 respondents. Random sampling techniques are used to determine respondents. The study found that Investment Interest is more primarily shaped by financial literacy than Financial Attitude to improve investment decisions